Digital Workforce Transformation : Upskilling Strategies for the Future of Work - Emre Aksoy; Selin Kaya (Digital Innovation : International Journal of Management, 2024)
This research focuses on strategies for upskilling the workforce to meet the demands of a digital economy. By analyzing corporate training programs and industry trends, the study identifies effective approaches for reskilling employees in areas like AI, data analytics, and digital marketing. Findings suggest that continuous learning is essential for maintaining a competitive advantage in a rapidly evolving landscape.